School and society : - Tozer, Steven (McGraw-Hill, 2006)
Through the use of a consistent analytic framework, this text shows how and why certain school-society issues first arose in this country and how they have changed over time. Introduced and explained in detail in the first chapter, the text’s analytic framework focuses on the political economy, the dominant ideology, and existing educational practices that are prevalent in any given historical era. Readings at the end of each chapter are designed for the student to critique using the same analytic framework that the authors employ in the text. In its examination of the evolution of education in the United States, this book tells an engaging historical story.